An Analysis of the Integration of Faith- and Piety-Based (IMTAQ) Biology Learning to Strengthen Religious Moderation in Senior High Schools across Palembang City - Miftahussa’adiah, Miftahussa’adiah; Mini Sariwulan, RR; Putri Angggun, Diah; Amrullah, Fairuzzabadi; Fauzi Romadhan, Muhammad; Siyamto, Dimas; Aditya Ika Putri, Nindhita; Dwi Putri, Jesicha ‎; Asnilawati, Asnilawati; Afriansyah, Dini (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
Religious moderation is an important global issue in responding to the challenges of modern life, such as radicalism and intolerance. The integration of IMTAQ (Faith and Piety)–based biology learning is viewed as a strategic approach to strengthening religious moderation at the senior high school level. This study aims to analyze the integration of Islamic values in IMTAQ-based biology learning and its contribution to strengthening students’ religious moderation in public senior high schools across Palembang City. The study employed a mixed-methods approach with a sequential exploratory design, involving 12 senior high schools and 270 students. Data were collected through interviews, observations, analyses of instructional materials, and surveys. The results indicate comprehensive implementation, good to excellent learning quality, and positive student responses. IMTAQ-based biology learning has proven effective in supporting the strengthening of religious moderation through a holistic, inclusive, and meaningful approach. Analisis Integrasi Pembelajaran Biologi Berbasis Iman dan Taqwa (IMTAQ) dalam Memperkuat Moderasi Beragama di Sekolah Menengah Atas Negeri se-Kota Palembang ABSTRAK: Moderasi beragama merupakan isu global penting dalam merespons tantangan kehidupan modern seperti radikalisme dan intoleransi. Integrasi pembelajaran biologi berbasis IMTAQ (Iman dan Taqwa) dipandang sebagai pendekatan strategis untuk memperkuat moderasi beragama di jenjang sekolah menengah atas. Penelitian ini bertujuan menganalisis integrasi nilai-nilai Islam dalam pembelajaran biologi berbasis IMTAQ serta kontribusinya terhadap penguatan moderasi beragama peserta didik di Sekolah Menengah Atas Negeri se-Kota Palembang. Penelitian menggunakan pendekatan mixed methods dengan desain sequential exploratory, melibatkan 12 Sekolah Menengah Atas dan 270 peserta didik. Data dikumpulkan melalui wawancara, observasi, analisis perangkat pembelajaran, dan survei. Hasil penelitian menunjukkan implementasi yang komprehensif, kualitas pembelajaran yang baik hingga sangat baik, serta respons positif peserta didik. Pembelajaran biologi berbasis IMTAQ terbukti efektif mendukung penguatan moderasi beragama secara holistik, inklusif, dan bermakna